Green banking practices worldwide: prospects for Kazakhstan - Birzhanova, A.B.; Nurgaliyeva, A.M. (BUKETOV BUSINESS REVIEW, 2022)
Object: The article aims to explore the concept of “green banks” and review current worldwide developments in green banking with the emphasis on the Republic of Kazakhstan. Methods: Qualitative research methods: content analysis, abstraction, comparison, and generalization. Results: The paper explores definitions of “green banking” and categorization of green banking practices. Some of the popular internal and external green banking activities are discussed. The authors found out that currently there is a global trend towards greening the banking sector. However, the scope of available green banking practices varies considerably across different countries and banks. The proposed greenness scale can be used to estimate banks’ activities from “slightly green” to “fully green banks”. Conclusions: While green bonds and green loans are widely discussed in the literature, the topic of green banking is mostly ignored. Since the Republic of Kazakhstan has stepped towards Green Economy, the prospects of green banking should not be neglected. To conform with sustainable development, commercial banks should engage in internal and external green banking practices. Government and responsible agencies (i.e., AIFC) should work closely with the commercial banks in the greening process.